Revision of Helvetia (Araneae: Salticidae: Heliophaninae) - Ruiz,Gustavo R. S. (2008)
The genus Helvetia Peckham & Peckham, 1894 is revised. The species H. zebrina Simon, 1901 and H. zonata Simon, 1901 are synonymized with H. cancrimana (Taczanowski, 1872). The species H. insularis (Banks, 1902) is synonymized with H. albovittata Simon, 1901. The genus Deloripa Simon, 1901 is considered a junior synonym of Helvetia by transfer of its type species, resulting in the new combination Helvetia semialba (Simon, 1901). The species Cotinusa humillima Mello-Leitão, 1943, transferred to Helvetia by Galiano, is revalidated. Helvetia roeweri (Soares & Camargo, 1948) comb. nov. is transferred from the genus Naubolus Simon, 1901. The epigynal structures of the type species H. santarema Peckham & Peckham, 1894 and those of H. semialba, H. albovittata, H. cancrimana and H. roeweri are illustrated, as well as the palp of H. humillima. Helvetia roeweri is redescribed and four new species are described: Helvetia labiata (Rio Grande do Sul, Brazil), Helvetia stridulans (Espírito Santo, Brazil), Helvetia rinaldiae (Pará and São Paulo, Brazil) and Helvetia galianoae (Misiones, Argentina). New records for H. cancrimana, H. albovittata and H. roeweri are given.